Digital Literacy Skills Against Children's Personal Data Protection on Social Media - Likha Sari Anggreni; Nunung Prajarto; Novi Kurnia (Ikatan Sarjana Komunikasi Indonesia, 2023)
The popularity of social media attracts many people to participate in various activities every day. Social media usually comes in the form of audio, graphics, video text and animations that provide convenience to its users to disseminate and access information quickly amd easily. Without realizing it, parents often show off their children's personal data in their parents' and children's accounts, usually for personal or business purposes. The purpose of this study is to examine more about the efforts made by parents to protect children's data privacy on Instagram social media accounts. This study uses the meta-analysis method of the literature study on previous studies. In this study, we want to see how the role of digital literacy in protecting children's personal data is and how to conceptualize children's self-protection digital literacy on social media. The findings of this study with the concept, threats, recommendations regarding the importance of digital literacy for personal data protection and conceptual integration can be used as a reference in further research. The protection of children's personal data is important to thwart the threat of cyber crime, violence and online extortion. It can also be one of the guarantees for children’s good growth and development because the data will not be misused by other parties for financial gain or to threaten children.